Ethanolic extraction of bioactive compounds from Vernonia amygdalina leaf using response surface methodology as an optimization tool - Alara, Oluwaseun Ruth; Nour, A. H.; Olalere, Olusegun Abayomi (Springer International Publishing, 2018)
In this study, ethanolic microwave-assisted extraction of total phenolic content (TFC), total flavonoid content (TFC) and antioxidant from Vernonia amygdalina leaf was investigated using response surface methodology. Four extraction variables, including irradiation time (1‒5 min), microwave power level (500‒700 W), feed-to-solvent ratio (1:8‒1:12 g/ml), and ethanol concentration (60‒80%) were optimized to obtain optimal yields. The analysis of variance results showed that ethanol concentration, microwave power level and irradiation time mostly affected the TFC, TPC and antioxidant activities significantly (p < 0.05), whereas the feed-to-solvent ratio was insignificant. The validated optimal yields of TPC (113.76 mg GAE/g d.w.), TFC (94.08 mg QE/g d.w.), DPPH (97.98%), and ABTS (99.34%) were obtained at extraction conditions, viz, 4 min of irradiation time, 558 W of microwave power, feed-to-solvent ratio of 1:10 g/ml, and ethanol concentration of 76%. In addition, the phytochemical profiling of the extract at optimal conditions confirmed the presence of phenolic and flavonoid compounds.